Politics and space in Antakya (2011-2019) - Burgaç Taş, Selin. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2022., 2022)
This thesis attempts to analyse the youth politics in the Armutlu neighbor hood, a predominantly Arab Alawi place in Hatay, between 2012 and 2015. Two pillars of the youth movement were the Syrian War (2011) and the Gezi Protests (2012). September 12, 2012, a pro-Assad demonstration was a break ing point for the Armutlu people and it immediately merged with the Antakya- Gezi movement. The Armutlu youth is the main actor in this anti-gov ernment protest. The political mobilization of the youth has generated a huge revision in their own Arab-Alawi identities as well asthe identity of the neigh borhood. Besides, it brought about the reconfiguration of the urban space in the neighbourhood. This thesis aims to bring the questions of identity, space and politics in an Alawi working- class neighborhood between 2012 and 2015. NOTE Keywords : Youth, Space and Place, Social Movements, Political Geography, Sect, Memory.
Keywords: Antioch (Turkey); Social life -- Hatay -- Defne.; Alevis -- Political activity -- Antioch (Turkey)